Rakta Kanchan (Bauhinia variegata): Chemistry, Traditional and Medicinal uses- a review - G.Mali, Ravindra; G.Mahajan, Shailaja; A.Mehta, Anita (Pharmacognosy Reviews)
Bauhinia variegata Linn. (Kanchnar / Rakta kanchan), is a widely used medicinal plant by the tribals throughout India and popular in various indigenous system of medicine like Ayurveda, Unani and Homoeopathy. Following the various traditional claims on utility of this plant in curing number of diseases, considerable efforts have been made by researchers to varify its utility through scientific pharmacological screenings. The notable biological activities reported are antitumour, antimicrobial, antiinflammatory, antigoitrogenic, hepatoprotective and haemagglutination. Industrially, the plant is widely used for the manufacture of woodwool board, production of gum and fibres. The plant is also utilized for afforestation to conserve the nature. This review presents a detailed survey of the literature on pharmacognosy, phytochemistry, traditional and biologically evaluated medicinal uses of B. variegata.